Peran Pendidikan Gerakan Pramuka Dalam Pembentukan Karakter Kepemimpinan Peserta Didik: Studi Kasus Di Madrasah Aliyah Negeri MAN 1 Kota Cilegon-Banten - arman munadi; Hartono Rudi (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2020)
Scout education is one of the non-formal education which is a place for the development of self-potential and has noble character, self-control, and life skills to give birth to the successors of the nation and state struggle. The process of character formation is an effort to help the mental development of children both physically and mentally. One non-formal education that can shape the character of leadership for students is extracurricular, especially scout education. The purpose of this research is to describe "the role of the scout movement education in the formation of students' leadership character" both in terms of independence, responsibility, discipline, and forming leadership character in the Madrasah Aliyah Negeri MAN 1 Cilegon City. This type of research uses qualitative methods with a descriptive approach. The subject of this research is the Scoutmaster, and students in front of the city of Cilegon 08.071-08072. Madrasah Aliyah Negeri MAN 1 Cilegon City. Data collection through observation techniques observation, interviews, documentation, and analyzing data. The results showed that Scouts were able to play a role in forming leadership character. alternative methods to instill and shape students' personalities in accordance with 18 national characters. It can be concluded that the role of the scout movement education is indeed quite significant as the formation of character, mentality or character The role of scouting will be more effective if it is given support in the form of good role models and habits from the surrounding environment.